The Policy Consequences of Health Bias in Political Voice. (March 2021) - Pacheco, Julianna
Although research on the link between health and political behavior at the individual level has flourished, there have been no systematic analyses regarding the policy consequences of health inequalities in political voice. Using a unique dataset that measures the health bias in voter turnout across the fifty states from 1996 to 2012, I find that state electorates that are disproportionately more representative of healthy citizens spend less on health and have less generous Medicaid programs. The negative relationship between the degree of health bias in state electorates and these outcomes remain after controlling for the degree of class bias in voter turnout. These findings have important implications for democratic theory and policy responsiveness, as well as our understanding of variations in population health and health policy across the American states.